Restricted health service utilization and subsequent positive self-care behavior during the early COVID-19 pandemic in China - Wang, Zhichao; Zhou, Zhongliang; Liu, Guanping; Lu, Jiao; Zhai, Xiaohui; Fan, Xiaojing; Lai, Sha; Wang, Youfa (Frontiers in Public Health, 2024)
Background: The reallocation of health resources, epidemic prevention and control measures during the COVID-19 pandemic triggered widespread restricted health service utilization, some residents and patients tried positive self-care behavior to maintain their health, yet the efficacy of this intervention remains unclear. Object: Based on the reasoned action approach (RAA) theory, this study aimed to investigate the correlation between self-care behavior and restricted health service utilization among adults in China, trying to discover the vulnerable groups and external and intrinsic factors that affect self-care behavior among Chinese adults. Methods: Data on demographics, socioeconomic, health status, and self-care behavior were collected in “The Early China COVID-19 Survey”, a cross-sectional anonymous online survey of the general population in China. Self-care behavior was measured by four indicators: weight control(WC), physical activity(PA), prevention behavior(PB), and Online medical consultation(OMC). The multiple linear models and binary logistic regression were used to examine whether restricted health service utilization (RHSU) is associated with self-care behaviors; also, adjusted multivariate logistic regression was used to analyse subgroup heterogeneity. Results: In total, 8,428 adult participants completed the survey, the mean OMC score was 1.51(SD 1.34), the mean PB score was 18.17 (SD 3.44), and the proportion of participants who engaged in WC and PA was 42.30% and 62.57%, respectively. According to the multiple regression model, the RHSU was significantly positively correlated with all four indicators of self-care(WC: OR=1.34, p<0.001, PA: OR=1.34, p<0.05, MC: OR=1.30，p<0.001, PB:coef=0.16, p<0.05). We also observed some significant differences in the intensity of this relationship by subgroup analysis, precisely, OMC(high vs. moderate vs. low infection-risk level: OR=1.48; 1.41; 1.19, p<0.1), PA(male vs. female: OR=1.27;1.06;p<0.001, high vs. Moderate and low infection-risk level: OR=1.51;1.17;1.02, p<0.05), PB(Chronic disease groups vs. no: coef=0.46;0.1, p<0.05). Conclusions: Restricted health service utilization predicts more positive self-care behavior, and the intensity of partial correlation was significantly different in the subgroups of sex, living area infection risk levels, and chronic diseases. These findings highlight the urgent demand for self-care behavior among Chinese adults during the pandemic and provide new insights for developing self-care and reducing the burden on the healthcare system in the long term.